USER INTERFACE AND USER EXPERIENCE DESIGNING IN THE KAPUSTAKAN SYSTEM USING USER CENTRED DESIGN APPROACH (CASE STUDY: KERATON NGAYOGYAKARTA HADININGRAT) - Mina Rofida Rahmatina; Chanifah Indah Ratnasari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2022)
The Kapustakan System is a digital collection management system for the Keraton Ngayogyakarta Hadiningrat. The Kapustakan System is being developed to present various museum collections in digital representation, facilitating access to knowledge search, cross-referencing, and encouraging research. This system needs an interface design that takes into account both the User Interface (UI) and the User Experience (UX) to make users feel comfortable when they use it. This paper describes the UI/UX design process for the Kapustakan System using the user-centred Design (UCD) method, which consists of five stages: planning the human-centred design, specifying the context of use, specifying user and organizational requirements, producing design solutions, and evaluating designs against user requirements. The UCD method focuses on the direct involvement of prospective users so that they can influence the design results that meet their needs and desires. The result of this research is a prototype design of the Kapustakan System that has been validated through usability testing of potential users. The parameters tested in usability testing are success rate, efficiency, error rate, and satisfaction. The test's success rate is 93.75%, its efficiency is 90.27%, its error rate is 3.73%, and its satisfaction is 86.25.